2018
DOI: 10.1111/cea.13157
|View full text |Cite
|
Sign up to set email alerts
|

FcεRI expression and IgE binding by dendritic cells and basophils in allergic rhinitis and upon allergen immunotherapy

Abstract: This study provides a comprehensive insight into the relation between serum IgE and FcεRI/IgE on basophils and DC subsets. The novel finding that HDM SCIT induces a temporary increase in FcεRI expression on DCs, but not on basophils, can be an incentive for future research on the potential tolerogenic role of IgE/FcεRI signalling in DCs in the setting of allergen immunotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 64 publications
2
22
0
Order By: Relevance
“…The expression of high-affinity receptors can be elevated in response to increasing serum IgE. Irrespective of allergic status, IgE primarily binds to basophil rather than DC receptors [45]. Just recently, it was demonstrated that upon allergen exposure, increases in serum IgE are accompanied by expansion of IgE + plasmablasts.…”
Section: Early Phase Responsesmentioning
confidence: 99%
“…The expression of high-affinity receptors can be elevated in response to increasing serum IgE. Irrespective of allergic status, IgE primarily binds to basophil rather than DC receptors [45]. Just recently, it was demonstrated that upon allergen exposure, increases in serum IgE are accompanied by expansion of IgE + plasmablasts.…”
Section: Early Phase Responsesmentioning
confidence: 99%
“…Further, it's the degranulation of mast cells and basophils that leads to allergic inflammation and symptoms, like nasal congestion, itchy nose and ocular pruritus directly, but activity of mast cells and basophils is influenced by many factors besides activated T cells. It was found that serum sIgE/tIgE ratio may determine the density of FcɛRI-bound allergen sIgE and therefore the likelihood of allergens to cross-link FcɛRI and to induce basophil activation in allergic subjects [33]. MCs activation are mainly mediated by cross-linking of allergen-sIgE complexes and FcεRI receptors on the membrane surface of MCs [34], in some cases allergen specific IgGs can crosslink FcεRI bound allergen-IgE complexes and aggravate allergic inflammation [30].…”
Section: Discussionmentioning
confidence: 99%
“…Using this approach, we identified FcεRIα expression on pDCs, monocytes, cDCs and basophils ( Figure 1D), as previously demonstrated. 23 To investigate the association between atopy and asthma with performed as a way of interrogating trends observed within each individual cohort. Once combined, we observed an increased proportion of FcεRIα + pDCs in atopic/asthmatics compared to atopic/ non-asthmatics ( Figure 2C) and we also observed significantly greater FcεRIα expression levels on FcεRIα + pDCs, cDCs and basophils in atopic individuals (non-asthmatic and asthmatic) compared to non-atopic/non-asthmatics ( Figure 2D).…”
Section: Re Sultsmentioning
confidence: 99%